(untitled) (Nigerian Journal of Technology, 2024)
Passenger’s waiting time at terminal is a key constituent of travel time, as long waiting time increases the overall journey time. In Nigeria, urban-rural bus transit system is associated with long waiting time. This study evaluates bus transit users’ waiting times at terminal with perceived and actual waiting times (PWT and AWT) along with associated bus service frequency (BSF). Bus public transit operating from Enugu city (as origin) to 6 local government areas (Awgu, Isi-Uzo, Nkanu west, Nsukka, Oji River and Udenu) of the state as destinations was studied. Data were collected on AWT and PWT at Old Park, Enugu for 30 days from 8 am to 6 pm (5 days per route). Data on AWT and PWT were collected based on passenger’s observation and oral interview, respectively. The study discovered that transit users incurred long waiting times, with 80 – 90% of the users incurring AWT of 21 minutes to 1 hour and more, indicating a poor service quality. Also, 80 – 90% of the users overestimated their PWT by 25 – 60%. At 95% confidence level, PWT is significantly longer than AWT (P < 0.05) for all the routes. A passenger’s perceived waiting time model was developed for predicting PWT based on AWT. The model developed showed that PWT is strongly correlated with AWT, with an R2 = 0.9591 and F-significance < 0.05. This suggests that that AWT accounts for 96% variability in PWT. Consequently, the model developed exhibits a reasonable accuracy, hence, can be applied for prediction of passenger’s perceived waiting time. The mean BSF for Enugu – Nsukka and Enugu – Oji River routes were 30 and 21 buses per day, respectively. While, the other 4 routes recorded lower values of 7 – 9 buses per day, resulting in longer waiting times than the other 2 routes. The implication of long passengers’ waiting time suggests the need for shifting from unscheduled to scheduled operation and improved BSF by shortening bus headways to minimize waiting time.